Behaviour of Factors II, VII, IX, and X during Long-Term Treatment with Coumarin - Loeliger, E. A; van der Esch, B; Mattern, M. J; den Brabander, A. S. A (Thrombosis and Haemostasis, 1963)
During long-term treatment with the long-acting coumarin derivative phenprocoumarol (marcoumar) no statistically significant difference in the depression of the activity of coagulation factors II, VII, IX, and X was found. The shorter-acting anticoagulants acenocoumarol (sintrom), warfarin sodium (coumadin), and dicoumarol, possibly lower factor IX somewhat less and factor X somewhat more than they do factors II and VII.A 2.5-fold prolongation of the “prothrombin” time (using Owren 5 s human brain thromboplastin) and the same prolongation of the thrombotest time appear to correspond with a depression of all four factors from 100% down to approximately 20’%, the normal standard being a mixed population with a mean age of 29 years.Separate determination of one of the four coagulation factors concerned is pointless; “prothrombin” time estimation, and more specifically thrombotest, still remain the most reliable methods for controlling the anti-vitamin K action of anticoagulants during long-term treatment.